2019
DOI: 10.1073/pnas.1916119117
|View full text |Cite
|
Sign up to set email alerts
|

Switching sides—Reengineered primary charge separation in the bacterial photosynthetic reaction center

Abstract: We report 90% yield of electron transfer (ET) from the singlet excited state P* of the primary electron-donor P (a bacteriochlorophyll dimer) to the B-side bacteriopheophytin (HB) in the bacterial photosynthetic reaction center (RC). Starting from a platform Rhodobacter sphaeroides RC bearing several amino acid changes, an Arg in place of the native Leu at L185—positioned over one face of HB and only ∼4 Å from the 4 central nitrogens of the HB macrocycle—is the key additional mutation providing 90% yield of P+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 74 publications
8
42
0
Order By: Relevance
“…2d). This trend is qualitatively consistent with the experimental observations for the mutant PbRC, [47][48][49][50]52 where the calculated time constant ($118 ps) is quantitatively larger than the experimental values ($16 ps). 47 Here, only the local geometry of Phe-M210 was optimized in QM/MM, xing surrounding proteins at the original geometry of wild type, although the mutation may also affect the surrounding geometry.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…2d). This trend is qualitatively consistent with the experimental observations for the mutant PbRC, [47][48][49][50]52 where the calculated time constant ($118 ps) is quantitatively larger than the experimental values ($16 ps). 47 Here, only the local geometry of Phe-M210 was optimized in QM/MM, xing surrounding proteins at the original geometry of wild type, although the mutation may also affect the surrounding geometry.…”
Section: Methodssupporting
confidence: 90%
“…The previous time-resolved spectroscopic measurements of mutant PbRC suggested that some specic residues especially contribute to unidirectional charge separation. [47][48][49][50]52 We have extensively analyzed the contribution of each residue to the potential shi on the pigments one by one, and concluded that Tyr-M210 near B L has the largest contribution to the stabilization of B L c À , 33,34 where Phe-L181 is located at the counterpart position near B M .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S20 and Table S4). This biexponential P* decay and P + HAformation has been noted previously in the literature for WT RCs (6,10,15,18,19,44,45).…”
Section: Verification Of Ncaa Incorporation and Minimal Structural Perturbationsupporting
confidence: 85%
“…An alternative model for ET has been proposed in which P* transfers an electron to HA directly through a superexchange mechanism, in which the BA chromophore mediates the electronic coupling between P* and HA. For wild-type (WT) RCs evidence favors 2-step ET at room temperature (1,12,13,15,16). It has been previously proposed that minor degrees of superexchange occur in WT RCs, likely arising from or enhanced by the inherent distribution in the energies of P*, P + BA -, and P + HAcaused by protein populations with slight variations in amino acid nuclear coordinates around chromophores (5,(17)(18)(19), but this has been difficult to study experimentally (1,12).…”
Section: Introductionmentioning
confidence: 99%